Langerin-mediated internalization of a modified peptide routes antigens to early endosomes and enhances cross-presentation by human Langerhans cells - Fehres, Cynthia M; Duinkerken, Sanne; Bruijns, Sven CM; Kalay, Hakan; van Vliet, Sandra J; Ambrosini, Martino; de Gruijl, Tanja D; Unger, Wendy WJ; Garcia-Vallejo, Juan J; van Kooyk, Yvette (Cellular & molecular immunology, 2017)
The potential of the skin immune system to generate immune responses is well established, and the skin is actively exploited as a vaccination site. Human skin contains several antigen-presenting cell subsets with specialized functions. In particular, the capacity to cross-present exogenous antigens to CD8^＋ T cells is of interest for the design of effective immunotherapies against viruses or cancer. Here, we show that primary human Langerhans cells （LCs） were able to cross-present a synthetic long peptide （SLP） to CD8^＋ T cells. In addition, modification of this SLP using antibodies against the receptor langerin, but not dectin-1, further enhanced the cross-presenting capacity of LCs through routing of internalized antigens to less proteolytic early endosome antigen 1 ^＋ early endosomes. The potency of LCs to enhance CD8^＋ T-cell responses could be further increased through activation of LCs with the toll-like receptor 3 ligand polyinosinic：polycytidylic acid （phC）. Altogether, the data provide evidence that human LCs are able to cross-present antigens after langerin-mediated internalization. Furthermore, the potential for antigen modification to target LCs specifically provides a rationale for generating effective anti-tumor or anti-viral cytotoxic T lymphocyte responses.